2019
DOI: 10.1111/pde.13741
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome in preadolescent acne: Assessment and prospective analysis of the influence of benzoyl peroxide

Abstract: Background/Objectives The pathogenesis of preadolescent acne has not been well studied, and it is uncertain if Cutibacterium acnes is a predominant organism in the microbiome in this age group. The aim of this study was to analyze the microbiome of preadolescent females and to assess whether benzoyl peroxide impacts the microbiome. Methods The study enrolled girls, aged 7‐12 years, with evidence of at least six acne lesions who had not been previously treated. Participants’ skin surface of forehead, cheeks, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
21
0
2
Order By: Relevance
“…As regards alternative treatments to isotretinoin and antibiotics, a study by Ahluwalia et al in 2019 indicated that the antiseptic benzoyl peroxide (BPO), an over-the-counter acne treatment with bactericidal, anti-inflammatory, and comedolytic properties, did not affect microbial diversity [45]. However, these data need to be confirmed as a smaller-sized study-including only five preadolescent females with acne treated with BPO-found that microflora diversity decreased after treatment [46].…”
Section: Systemic and Topical Antibiotics Induce Cutaneous Dysbiosismentioning
confidence: 99%
“…As regards alternative treatments to isotretinoin and antibiotics, a study by Ahluwalia et al in 2019 indicated that the antiseptic benzoyl peroxide (BPO), an over-the-counter acne treatment with bactericidal, anti-inflammatory, and comedolytic properties, did not affect microbial diversity [45]. However, these data need to be confirmed as a smaller-sized study-including only five preadolescent females with acne treated with BPO-found that microflora diversity decreased after treatment [46].…”
Section: Systemic and Topical Antibiotics Induce Cutaneous Dysbiosismentioning
confidence: 99%
“…Atopic dermatitis (AD) is a chronic, recurrent inflammatory skin disease that commonly occurs in children but can also affect adults [ 41 , 42 , 43 ]. The incidence of AD is increasing, and this disease is thought to affect 5–20% of children and 1–3% of adults worldwide [ 41 , 42 ].…”
Section: The Skin Microbiome In Patients With Atopic Dermatitismentioning
confidence: 99%
“…Atopic dermatitis (AD) is a chronic, recurrent inflammatory skin disease that commonly occurs in children but can also affect adults [ 41 , 42 , 43 ]. The incidence of AD is increasing, and this disease is thought to affect 5–20% of children and 1–3% of adults worldwide [ 41 , 42 ]. Microbiome studies in patients with AD have shown reduced biodiversity of bacterial communities and a significant increase in colonization by Staphylococcus aureus , compared with healthy subjects, in whom colonization by this species is rare.…”
Section: The Skin Microbiome In Patients With Atopic Dermatitismentioning
confidence: 99%
“…did not significantly affect the presence of skin commensals. 215,216 From the acne literature, daily use of BPO washes on the face did not change microbial diversity, 217 but daily application of a BPO containing cream did decrease α-diversity. 218 As epidemiological data indicate that increases in the number of prescriptions and antibiotic use are closely followed by increased antibiotic resistance, it becomes even more relevant to determine which microbes are critical players in HS pathophysiology.…”
Section: The Impac T Of Antib I Oti C S On the S K In Microb I Omementioning
confidence: 99%